2014
DOI: 10.1177/0049124114546904
|View full text |Cite
|
Sign up to set email alerts
|

Review of Estimation Methods for Landline and Cell Phone Surveys

Abstract: The rapid proliferation of cell phone use and the accompanying decline in landline service in recent years have resulted in substantial potential for coverage bias in landline random-digit-dial telephone surveys, which has led to the implementation of dual-frame designs that incorporate both landline and cell phone samples. Consequently, researchers have developed methods to allocate samples and combine the data from the two frames. In this article, we review point and interval estimation methods of proportion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
(18 reference statements)
2
5
0
Order By: Relevance
“…These results are similar to the findings by Skinner and Rao (1996) and Lohr and Rao (2000). These authors have suggested that when there is little empirical evidence to select a preferred estimator, the decision to choose one estimator over the others should be made on theoretical and practical considerations, such as internal consistency and the availability of good-quality poststratification raking for benchmarking (Brick 2013;Arcos et al 2014). …”
Section: Resultssupporting
confidence: 83%
“…These results are similar to the findings by Skinner and Rao (1996) and Lohr and Rao (2000). These authors have suggested that when there is little empirical evidence to select a preferred estimator, the decision to choose one estimator over the others should be made on theoretical and practical considerations, such as internal consistency and the availability of good-quality poststratification raking for benchmarking (Brick 2013;Arcos et al 2014). …”
Section: Resultssupporting
confidence: 83%
“…In those patients whom we had the opportunity to time, survey completion occurred at an average of 7 minutes, which may have decreased the accuracy of survey responses as a result of patient fatigue. 38 Similar to previous studies, this study has limited generalizability to nonacademic medical centers. 10,21 Incomplete RPDR administrative data also limited the results of this study.…”
Section: Figurementioning
confidence: 85%
“…While there is general agreement that non-coverage bias is reduced through inclusion of the mobile-only population ( Blumberg and Luke, 2009 , Mohorko et al, 2013 ), possible duplication of survey participants using both landline and mobile telephones (dual-users) adds complexity. This overlap is addressed through weighting strategies ( Hartley, 1974 ), however, there is no agreed consensus as to the optimal estimator ( Arcos et al, 2015 ). Furthermore, the choice of estimator is influenced by the type of information available about the mobile telephone population.…”
Section: Introductionmentioning
confidence: 99%